Effect of Siberian Ginseng Water Extract as a Dietary Additive on Growth Performance, Blood Biochemical Indexes, Lipid Metabolism, and Expression of PPARs Pathway-Related Genes in Genetically Improved Farmed Tilapia (Oreochromis niloticus) - Mingxiao Li; Jun Qiang; Xiaowen Zhu; Jingwen Bao; Yifan Tao; Haojun Zhu (Fishes, 2022)
Overnutrition in high-density aquaculture can negatively affect the health of farmed fish. The Chinese herbal medicine Siberian ginseng (Acanthopanax senticosus, AS) can promote animal growth and immunity, and regulate lipid metabolism. Therefore, we conducted an 8-week experiment, in which Oreochromis niloticus was fed with a diet supplemented with different concentrations of AS water extract (ASW) (0‰, 0.1‰, 0.2‰, 0.4‰, 0.8‰, and 1.6‰). The ASW improved the growth performance and increased the specific growth rate (SGR). Linear regression analysis based on the SGR estimated that the optimal ASW amount was 0.74‰. Dietary supplementation with 0.4–0.8‰ ASW reduced the triglyceride and total cholesterol levels in the serum and liver, and regulated lipid transport by increasing the high-density lipoprotein cholesterol concentration and lowering the low-density lipoprotein cholesterol concentration. Dietary supplementation with ASW increased the activities of superoxide dismutase and catalase in the liver, thereby improving the antioxidant capacity. Moreover, ASW modulated the transcription of genes in the peroxisome proliferator-activated receptor signaling pathway in the liver (upregulation of PPARα, APOA1b, and FABP10a and downregulation of PPARγ), thereby regulating fatty acid synthesis and metabolism and slowing fat deposition. These results showed that 0.4–0.8‰ ASW can slow fat deposition and protected the liver from cell damage and abnormal lipid metabolism.